Pengembangan Profil Perusahaan Rumah Tahsin Ash Habul Qur’an Kartasura Berbasis Web - Galuh Pravitasari, Suryanti; Tri Vulandari, Retno; Isnan Nurrohman, Muhammad; Abyan Zakly, Faris (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2024)
The creation of a Web profile for Rumah Tahsin Ash Habul Qur'an, Sukoharjo is to introduce Rumah Tahsin Ash Habul Qur'an, Sukoharjo which aims to provide information to the public so that the public is more aware of the existence and development of Rumah Tahsin Ash Habul Qur'an, Sukoharjo. In addition, this web profile aims to facilitate public access to information about Rumah Tahsin Ash Habul Qur'an, Sukoharjo, as well as a publication media for the village government to convey various work programs, reports, and information to the community. The data collection methods carried out by the author include interviews, observations and literature studies. The interview was conducted with the village secretary. Observations are carried out to match data and anticipate new information at the research location, so that actual and reliable data and information are obtained. Meanwhile, literature studies are useful for obtaining a theoretical foundation in the form of experts regarding the subject of research. The steps to create this web project are pre-production, production, post-production